Does stream of education affect the knowledge and attitude regarding breastfeeding among adolescent students? - Bhattacharya, Sudip; Singh, Amarjeet; Prakas, Kiran h (Indian Journal of Community Health, 2016)
Background: The benefits of breastfeeding are accepted universally. Inadequate knowledge, or unfavourable attitude, affects future perception of women toward breastfeeding during adolescence. Aims & Objectives: (1) To compare the knowledge and attitude regarding breastfeeding among fresh graduates (science versus other streams) and (2) To analyse the syllabus of breastfeeding-related topics during formal education in schools. Material & Methods: This cross-sectional study was conducted among teenage college students (n = 187) in Chandigarh. Knowledge and attitude of students from science versus other (arts and commerce) streams about breastfeeding were assessed using a questionnaire. The authors also analysed the syllabus of science. Descriptive statistical analysis was done by SPSS(V-16). Item wise chi- square test was applied. Results: Almost all students knew the benefits of breastfeeding irrespective of the stream. Some knowledge gaps were noticed. Majority (69.2%) from others stream considered breast milk as unhygienic. Some (30.8%) of them believed that small breasts produce insufficient milk. Science stream students (63.4%) were more confident about their future breastfeeding. Most of the other group students (96.2%) did not know the preventive role of breastfeeding. Breastfeeding topic is inadequately discussed in schools. Conclusion: Students from science stream had better knowledge and favourable attitude toward breastfeeding.